Antibacterial and photocatalytic active transparent TiO2 crystallized CaO–BaO–B2O3–Al2O3–TiO2–ZnO glass nanocomposites. Issue 6 (3rd December 2018) - Singh, Gurpreet; Kumar, Sandeep; Sharma, Sumeet K.; Sharma, Moolchand; Singh, Vinay P.; Vaish, Rahul
Abstract: Transparent TiO2 crystallized 5CaO–10BaO–65B2 O3 –Al2 O3 –20TiO2 –10ZnO (CBBATZ) glass nanocomposites were fabricated using melt‐quenching technique followed by specific heat treatments. As‐quenched glass samples were provided three different heat treatments at 630°C for 3, 5, and 10 hours in order to obtain different amounts of TiO2 nanocrystals in the glass. The presence of rutile phase of TiO2 nanocrystals in glass was confirmed by X‐ray diffraction. The glass nanocomposite heat treated for 10 hours showed a hydrophobic nature with contact angle of 90.90°. Contact angle decreased from 90.90 to 22.20°, when irradiated under ultraviolet (UV) radiation for 45 minutes. This photoinduced hydrophilicity showed a photocatalytic and self‐cleaning properties of glass nanocomposite. During photocatalytic ink test, the maximum change in color of Resurin (Rz) ink and 60% degradation in absorbance of ink within 150 minutes under UV radiation were found for glass nanocomposite heat treated at 10 hours. Also, 78% degradation in absorbance of methylene blue dye (pollutant) within 180 minutes under UV irradiation was found for glass naocomposite heat‐treated at 10 hours. Antibacterial performance of transparent glass nanocomposite against Escherichia coli was evaluated as well. More than 95% of the bacterial cells were degraded with glass nanocomposite heat‐treated at 10 hours. CBBATZ glass nanocomposite found to impart the antibacterial effect through generation of reactive oxygen species (ROS) in aqueous medium. ROS species which was confirmed in the bacterial cell through intracellular ROS generation kit. During evaluation of mechanical properties using nanoindentation technique, the values of hardness and reduced modulus increased by ~26% and 10%, respectively, for glass nanocomposite heat‐treated at 10 hours as compared to as‐quenched glass.